2018
DOI: 10.1177/1094342018797170
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a scalable, performance portable shallow water equation solver using radial basis function-generated finite difference methods

Abstract: In this article, we describe and analyze the computational performance of a parallel shallow water equation (SWE) solver for atmospheric simulation using radial basis function-finite difference (RBF-FD) methods. The inherent "meshless" nature of RBF-FD methods provides significant numerical benefits over standard pseudospectral and traditional FD methods, but there are many challenges in terms of their performance and parallel implementation, due to RBF-FDs use of relatively large halos and unstructured indexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Over the last decades, RBF-FD methods have been successfully applied to a wide range of problems in science and engineering. Some of the application areas include the geosciences [16,17,18], combustion modelling [19,20], PDEs on surfaces [21,22,23], interface [24,25] and contact [26] problems, as well as scalable high-performance implementations [27,28,29]. For a complete list of references see monograph [14].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, RBF-FD methods have been successfully applied to a wide range of problems in science and engineering. Some of the application areas include the geosciences [16,17,18], combustion modelling [19,20], PDEs on surfaces [21,22,23], interface [24,25] and contact [26] problems, as well as scalable high-performance implementations [27,28,29]. For a complete list of references see monograph [14].…”
Section: Introductionmentioning
confidence: 99%
“…Such a scheme would avoid computing the weights of already mapped stencils, thus increasing the overall performance of the method. Moreover, recent studies have shown promising solutions for solving RBF-FD stencils in parallel by using point indexing (ELLIOTT et al, 2019), which would be another alternative to be investigated for our framework.…”
Section: Lookup Tablementioning
confidence: 99%